Implementation Of Prophetic Communication Of The Head Of Man Medan City (Multi-Site Study In MAN Medan) - Umi Kalsum; Mesiono; Achyar Zein (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
This study aims to: 1) Analyze the prophetic communication method of the Madrasah Principal at MAN Kota Medan; 2) Analyze the role of the Madrasah Principal in implementing prophetic communication; 3) Identify supporting and inhibiting factors; and 4) Understand the prophetic communication model applied. The approach used is qualitative with a case study type and multi-site design. A qualitative approach with a multi-site case study method is used to deeply understand the application of the communication model. Data were collected through observation, in-depth interviews, and documentation studies, and analyzed using a cross-site analysis approach. The results of the study indicate that the Madrasah Principal at MAN Kota Medan applies prophetic communication based on exemplary behavior, compassion, wisdom, and empathy. Although all madrasahs refer to the principles of communication of the Prophet Muhammad SAW, each has its own uniqueness in its implementation. The role of the madrasah principal is identified as a communicative, solution-oriented, and spiritual role model, and contributes to the formation of an Islamic and harmonious madrasah culture. Supporting and inhibiting factors for prophetic communication were found to be related to leadership, madrasah culture, and HR competency. Each madrasah shows its uniqueness: MAN 1 excels in the culture of deliberation and religious programs, MAN 2 in interpersonal relationships and teacher competence, and MAN 3 in the adaptation of technology based on prophetic values. The prophetic communication model applied includes the principles of Qaulan Sadidan, Qaulan Balighan, Qaulan Maisuran, Qaulan Layyinan, Qaulan Kariman, and Qaulan Ma'rufan. This model creates a harmonious, supportive, and productive madrasah environment, while creating a learning atmosphere that is conducive to students' academic and spiritual development.